Examining Industrialization or Environment Issues: Policy Analysis of Green Land Conversion in Batu City - Salsabila, Muhammad Ihwan; Ruhunussa, Muhammad Alsafik; Ikhwansyah, Erlangga; Roziqin, Ali (Journal Public Policy, 2025)
This research focuses on environmental sustainability which is an important aspect to maintain in sustainable development. The conversion of green land into coffee shops in Batu City has an impact on the local economy, while it hurts environmental sustainability. This research aims to analyze how the policy of the government in the Batu City area is more leaning towards the issue economy or sustainability environment life. This research used a qualitative with approach case studies. Data collection was obtained from two types of data, primary through observations and interviews as well as secondary data through documentation. The study found that there is no local government policy that specifically addresses the conversion of green land into coffee shops, which has a significant negative impact on the environment. Therefore, there needs to be government attention to the environment (environmental governance) through the formulation of environmental policies, mechanisms to support green land investment, and commitment and cooperation of stakeholders to oversee environmental sustainability. Therefore, sustainable development that integrates economic and environmental interests which is required. The conclusion is that no local government policy is in place to deal with the conversion of green land to the coffee shop industry and that the local government policy in Batu City tends to focus on economic issues rather than environmental sustainability.